Increasing food diversity and nutritional yield: evaluating diverse cropping systems. A field study in Rajshahi District in Bangladesh - Saiful Islam; Cheesman, Stephanie; Maruf Hossen Shanto; Hossain, Shakhawat; Md. Arifur Rahaman; Hossain, M. Khaled; Gathala, Mahesh Kumar; Krupnik, Timothy J. (TAFSSA, 2024)
This research brief presents findings on the nutritional yield (NY) of macro and micronutrients from various cropping system options. The studied systems included: Rice-Lentil-Sweet Corn, Rice-Maize intercropped with red amaranth and sorghum (as fodder), Rice-Mustard intercropped with sorghum and cowpea (as fodder), and the conventional Rice-Mustard-Fallow system. These systems were assessed to promote dietary diversity and healthier food options. The Rice-Mustard-Fallow system is traditionally followed by farmers, while the other three represent more intensive and diverse cropping alternatives. The study was carried out across 40 farmers' fields in two villages in the Rajshahi district of Bangladesh.